A Prospective Interventional Study to Compare Induction Chemotherapy Followed by Definitive Chemoradiation Versus Definitive Chemoradiation in Locally Advanced Carcinoma Cervix Patients - Saini, Naresh Kumar; Meena, Chetna; Mehta, Harsha N; Gothwal, Ravinder Singh; kumawat, Suman; Dadheech, Apoorva; Mundel, Suman (Asian Pacific Journal of Cancer Care, 2024)
Background: Cervical cancer is the fourth most commonly diagnosed cancer and the fourth leading cause of cancer death in women worldwide. Every year in India, 1,23,907 women are diagnosed with cervical cancer and 77,348 die from the disease. In India majority of patients of carcinoma cervix presented in locally advanced stage. Chemoradiation followed by brachytherapy is the standard of care for management of locally advanced cervical cancer but failure to control systemic disease occurs in one third of patients. Neoadjuvant chemotherapy, however, has been tested in various studies in cervical cancer for many years without success. In this study, we compared induction chemotherapy with 3weekly paclitaxel and cisplatin followed by chemo-radiation versus definitive chemo radiation. Materials and Methods: In this study 100 histopathologically proven squamous cell carcinoma cervix, locally advanced patients were included,the study group (n=50) received induction chemotherapy followed by definitive chemoradiation while the control group (n=50) received definitive chemoradiation. Results: The median age was 51 years (Range 32 – 65 years). Majority of patients was FIGO stage IIB (23%), IIIB (61%). In study arm 42 patients (84%) had complete response, and 7 patients (14%) had partial response. In control group 40 patients (80%) had complete response and 8 patients (16%) had partial response. Overall response rate was 98% in study group and 96% in control group. (p value=0.991, statistically insignificant). Grade 2 and 3 haematological toxicities were higher in study group as compare to control group. Among gastrointestinal toxicities (nausea, vomiting and diarrhea) grade 1 toxicity in study group and grade 2 toxicity in control group was slightly higher. (statistically insignificant). Conclusion: Induction chemotherapy with paclitaxel and cisplatin prior to standard chemoradiation provides similar results to chemoradiation alone with respect to response to treatment. Complete response rate was better achieved in study arm. In developing countries like India with limited resources and increasing cancer patient’s burden, induction chemotherapy followed by chemoradiation can be an alternative to standard care without compromising outcome and with manageable toxicities.